2022
DOI: 10.1186/s13023-022-02553-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation in GREB1L identified in a three-generation family with renal hypodysplasia/aplasia-3

Abstract: Background Renal hypodysplasia/aplasia-3 (RHDA3), as the most severe end of the spectrum of congenital anomalies of the kidney and urinary tract, is mainly caused by mutations in GREB1L. However, the mutations in GREB1L identified to date only explain a limited proportion of RHDA3 cases, and the mechanism of GREB1L mutations causing RHDA3 is unclear. Results According to whole-exome sequencing, a three-generation family suffering from RHDA3 was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…RDH types 1, 2, and 3 have been attributed to ITGA8 , FGF20 , and GREB1L , respectively. Renal Hypodysplasia/Aplasia 1 (RHDA1) is caused by homozygous or compound heterozygous mutations in ITGA8 (coding for integrin subunit alpha 8, critical in embryonic kidney development) or FGF20 17,62,105 . We previously discussed FGF20 and RHD2 in the section on BRA only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RDH types 1, 2, and 3 have been attributed to ITGA8 , FGF20 , and GREB1L , respectively. Renal Hypodysplasia/Aplasia 1 (RHDA1) is caused by homozygous or compound heterozygous mutations in ITGA8 (coding for integrin subunit alpha 8, critical in embryonic kidney development) or FGF20 17,62,105 . We previously discussed FGF20 and RHD2 in the section on BRA only.…”
Section: Resultsmentioning
confidence: 99%
“…GREB1L encodes for a protein likewise critical in the tubule development of the kidney, and in Wolffian and Mullerian duct formation. Associated with RDHA3, the most severe type of RDH, a heterozygous loss‐of‐function or missense variant in GREB1L can cause BRA, and mutations in this gene are also associated with other urogenital as well as skeletal, ear, and sometimes cardiac abnormalities 17,54,105 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our Q-PCR analysis showed that the point mutation in COL4A5 in the AS3 cell line was associated with a downregulation of this gene, and simultaneous upregulation of COL4A1 and LAMA1, supporting the idea that gene expression of the different collagen α chains is tightly controlled by quality check points. Moreover, the low expression of COL4A5 in the AS3 cell line may be due to excessive instability of the mutant mRNA (Roos and de Boer, 2021;Wu et al, 2022).…”
Section: Disrupted Pathways In Human Asmentioning
confidence: 99%